MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH TERHADAP PEMAHAMAN KOSAKATA BAHASA INDONESIA ANAK TUNARUNGU KELAS I DI SDLB - Cah Yusuf, Okki (Jurnal Pendidikan Khusus, 2017)
Abstract: Loss of hearing ability in children with hearing impairment results in deaf children experiencing obstacles in language development. The purpose of this study was to analyze the effect of pembelajan cooperative model of Make A Match against Indonesian vocabulary comprehension of deaf children in SDLB-B Karya Mulia II Surabaya. The subjects of this study are students of hearing impaired class I as many as eight students. This study used quantitative research methods, the design of Pre-Experimental Design with the kind of One-group pretest-posttest design. Data collected by using the test, Using the techniques of non-parametric statistical data analysis, according to the formula Wilcoxon Match Pair Test result shows the average value of 40.38 pretest and posttest average value of 69.93. While the results of data analysis showed that the value of zt = 1.96 and zh = 2.52 then the interprestation of Ha> Ho. So we can conclude Ha accepted, meaning that there is the influence of cooperative learning model of Make A Match tpie against Indonesian vocabulary comprehension of deaf children in SLB-B Karya Mulia II Surabaya.   Keywords: Make A Match, understanding the vocabulary of Indonesian